Evaluating Musculoskeletal Disorder Risk Factors through Quick Exposure Check: A Case Study in a Crumb Rubber Factory - Andhini Kumala; Muhammad Ilham Adelino; Meldia Fitri (Universitas Merdeka Malang, 2024)
Manual Material Handling (MMH) encompasses activities such as lifting, moving, carrying, pulling, and lowering materials or finished goods, relying on manual human power. The pressing workstation in the crumb rubber factory is a setting where MMH tasks are performed. Workers at this station are involved in lifting and moving bandelas weighing approximately 35 kg daily, without the aid of assistive devices, thereby exposing them to potential risks of musculoskeletal disorders. This study is designed to assess the work posture of employees at the pressing workstation concerning the risk of musculoskeletal disorders in the crumb rubber factory. The Quick Exposure Check (QEC) method was employed for evaluation, utilizing data collected through the QEC questionnaire from a total of 10 workers. The results showed that 80% of workers were at high risk of developing musculoskeletal disorders, characterized by an exposure level score of more than 70% and requiring improvement and change as quickly as possible. In contrast, 20% of workers showed exposure levels below 70% and required immediate remediation. This research contributes to increasing employee awareness of the risks of GMS and the importance of ergonomic work practices. This increased awareness can contribute to reducing the incidence of injuries and improving the welfare of workers in rubber factories.